2011
DOI: 10.1136/bcr.09.2011.4768
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral artery dissection in weightlifter with performance enhancing drug use

Abstract: This case report describes a transient ischaemic attack secondary to vertebral artery dissection (VAD) in a young male body builder. This occurred following weight training with weights across the back and shoulders. The patient was also known to take multiple performance enhancing agents including anabolic steroids, slimming agents, stimulants and human growth hormone. Cases of VAD have been described with cervical manipulation in the past and an association between the use of anabolic steroids and embolic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Recognition of this medical emergency is essential and the literature on the subject is, at present, very poor. A comprehensive review of the literature showed that, so far, only isolated cases or small series have been publish ed 2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24 . Of all the sports potentially related to cerebrum-cervical arterial dissection, scuba diving 25 and martial arts 20,21,22 are those that are most often mentioned in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition of this medical emergency is essential and the literature on the subject is, at present, very poor. A comprehensive review of the literature showed that, so far, only isolated cases or small series have been publish ed 2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24 . Of all the sports potentially related to cerebrum-cervical arterial dissection, scuba diving 25 and martial arts 20,21,22 are those that are most often mentioned in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Soccer 2 , diving 3,4 , wakeboarding 5 , golf 6 , treadmill running 7 , horse riding 8 , snowboarding 9 , physical fitness testing 10 , triathlon 11 , heavy weight-lifting 12,13 , volleyball 14 , basketball 15 , skating 16 , gymnastics 17 , tennis 18 and martial arts 19,20,21,22 are examples of these cases found in the literature. Even virtual sports, practiced using the Wii device, have been correlated with arterial dissections of the neck 23 .…”
mentioning
confidence: 99%
“…VAD has occurred in Australian football, 25 rugby, 25 tennis, 25 , 29 and soccer. 26 , 34 VAD has also been seen in horse racing, 10 weight lifting, 21 scuba diving, 19 inline skating, 16 trampoline jumping, 36 and gymnastics. 7…”
Section: Discussionmentioning
confidence: 99%